The role of eIF3 subunits in the mechanism of nonsense-mediated mRNA decay - Dias, Patrícia (2018)
Premature translation-termination codons (PTCs) or nonsense codons) can arise from mutations in germ or somatic cells. The introduction of a PTC into an mRNA can trigger nonsense-mediated decay (NMD), an important mRNA surveillance mechanism that typically recognizes and degrades mRNAs containing PTCs to prevent the synthesis of C-terminally truncated proteins potentially toxic for the cell. The physiological importance of NMD is manifested by the fact that about one third of genetic disease-associated mutations generate PTCs. The mammalian translation initiation factor 3 represents the most complex eukaryotic initiation factor (eIF) in mammalian cells. This factor comprises 13 subunits (eIF3a to eIF3m), each one playing an important role in translational control. Disruption of eIF3 initiation factor activity can lead not only to cancer but also neural physiological alterations, and to act as a mediator of infection cascade. Although some eIF3 subunits (for example, e and g) have been implicated in NMD, others were not studied yet. With the aim to identify other eIF3 subunits involved in NMD, we have depleted each one of the eIF3 subunits in HeLa cells and tested its effect in the expression of PTC-free or PTC- containing reporter human β-globin genes. Our data show that eIF3l and eIF3j subunits have an important role in targeting mRNAs for NMD. We will describe the molecular mechanisms underlying these observations.